Dietary Intake and Physical Activity of Medical School Students at Universitas Pelita Harapan, Indonesia - Dwi S. Rivami; Rohana U.P. Siregar; Neneng Suryadinata (Medicinus, 2025)
Background: Medical students face high academic demands, which often lead to irregular eating patterns and a lack of physical activity, which can have a negative influence on their nutritional status and overall well-being. This study aimed to evaluate the dietary intake and physical activity levels among medical students at Universitas Pelita Harapan, Indonesia. Methods: A cross-sectional study was conducted on 70 undergraduate medical students. Demographic data and physical activity levels (assessed using the International Physical Activity Questionnaire, IPAQ) were collected. Dietary intake was evaluated using a semi-quantitative food frequency questionnaire (SQ-FFQ), and nutrient intakes were analyzed and compared with the Indonesian Recommended Dietary Allowances (RDA) for women aged 19–29 years. Data analysis included descriptive statistics for continuous and categorical variables. Results: There were 70 participants, with a mean age was 20.73 ± 0.81 years; the majority were female (n = 62). Physical activity levels were distributed as 35.7% low, 38.6% moderate, and 25.7% high. Mean daily energy intake (1677.58 kcal) was below the RDA, as were intakes of fat, carbohydrates, fiber, calcium, sodium, potassium, and vitamin A. Intakes of protein, phosphorus, iron, vitamin C, riboflavin, and niacin were above RDA recommendations. Conclusions: Medical students at Universitas Pelita Harapan were found to have suboptimal dietary intake, particularly with regard to energy, fiber, and several micronutrients, as well as varying levels of physical activity. These findings emphasize the need for targeted interventions to promote balanced nutrition and regular physical activity in this population.